Media’s role in the crisis: a discursive comparison of U.S. media representations of unemployment in 2008 and 2020 - Yang, Ling; Yu, Lingli (Frontiers in Communication, 2025)
IntroductionThrough variations in reporting volume and discursive strategies, the media communicates risks to the public and shapes perceptions during crises.MethodsThis study conducted a corpus-based, quantitative analysis of topoi in American newspapers during the 2008 financial crisis and the 2020 COVID-19 pandemic, comparing media representations of unemployment.ResultsIt identifies four recurrent topoi common to both crises that characterize media coverage of unemployment. However, differences in other recurring topics reflect variations in the distinct causes of the crises, unemployment dynamics, and social policy responses.DiscussionThese findings highlight the media’s distinct influences on the evolution of each crisis and its portrayal of unemployment. By examining how media strategies shape discourse on unemployment, this study deepens our understanding of the interplay between media, discourse analysis, and crisis management during major economic disruptions.